2003
DOI: 10.1086/378383
|View full text |Cite
|
Sign up to set email alerts
|

The Environment of Active Galactic Nuclei in the Sloan Digital Sky Survey

Abstract: We present the observed fraction of galaxies with an active galactic nucleus (AGN) as a function of environment in the early data release of the Sloan Digital Sky Survey (SDSS). Using 4921 galaxies in the redshift range 0:05 z 0:095 and brighter than M r à ð Þ ¼ À20:0 (or M à þ 1:45), we find at least $20% of these galaxies possess an unambiguous detection of an AGN, but this fraction could be as high as '40% after we model the ambiguous emission-line galaxies in our sample. We have studied the environmental d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
305
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(361 citation statements)
references
References 58 publications
50
305
6
Order By: Relevance
“…dominated by Seyferts) with increasing galaxy environment density, mainly because the most powerful AGNs are hosted by late-type galaxies, which are the least likely to exist in dense environments. Popesso & Biviano (2006) found that the AGN fraction decreases with the increasing velocity dispersion of galaxies in groups and clusters, being higher in dense, low-dispersion groups, in contrast to the findings of Shen et al (2007) & Miller et al (2003) who found that the frequency of low activity AGNs does not correlate with environment.…”
Section: Introductionmentioning
confidence: 78%
“…dominated by Seyferts) with increasing galaxy environment density, mainly because the most powerful AGNs are hosted by late-type galaxies, which are the least likely to exist in dense environments. Popesso & Biviano (2006) found that the AGN fraction decreases with the increasing velocity dispersion of galaxies in groups and clusters, being higher in dense, low-dispersion groups, in contrast to the findings of Shen et al (2007) & Miller et al (2003) who found that the frequency of low activity AGNs does not correlate with environment.…”
Section: Introductionmentioning
confidence: 78%
“…More recently, Miller et al (2003) found from SDSS data that a very high fraction of galaxies host an AGN (∼ 20 − 40%) suggesting lifetimes longer than previously thought (i.e. > 10 8 yr).…”
Section: The Lifetime Of Active Bh'smentioning
confidence: 87%
“…There have been several studies identifying AGNs spectroscopically from different subsamples of SDSS galaxies ( Kauffmann et al 2003a;Miller et al 2003). Both studies have focused on narrow-line AGNs identified from the diagnostic diagrams.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies have focused on narrow-line AGNs identified from the diagnostic diagrams. Miller et al (2003) found AGN signatures in at least 20% of 4921 galaxies in the redshift range 0:05 < z < 0:095 and studied the environment of these AGNs. Kauffmann et al (2003a) selected 22,623 narrow-line AGNs from a parent sample of 122,808 galaxies and studied their host galaxy properties.…”
Section: Introductionmentioning
confidence: 99%